UNDERGRADUATE STUDENTS’ PREFERENCE AND PERCEPTIONS ON THE USE OF QUILLBOT AND GRAMMARLY AS PARAPHASING TOOLS - Ade Risya Fitri; Utami Dewi (University of Kuningan, 2024)
Several investigations have studied how using Grammarly and QuillBot as paraphrase tools affects EFL students' writing and attitudes. However, students' preferences regarding these tools for paraphrasing students' writing in Indonesia still seem few and have not been explored much. This research aimed to determine which paraphrasing tools undergraduate students prefer for translating their text. This study used a qualitative case study approach. Questionnaires and in-depth interviews were used to investigate students' preferences as data collection tools. Fifteen students were selected by purposive sampling and were administered an online questionnaire. Then, students participated in in-depth interviews and obtained further information from an online questionnaire. The writer then analyzed the data using frequency and thematic analysis. The findings reveal that students prefer QuillBot over Grammarly for three reasons. First, they consider QuillBot to be an easy-to-access and time-saving tool. Second, QuillBot is a paraphrasing tool with various features that help students to paraphrase their writing. Third, QuillBot helps students avoid plagiarism and keep the originality of their writing. However, Grammarly also received high marks because it uses proper grammar when paraphrasing students' writing. Therefore, combining these two paraphrasing tools will make the students' writing process more efficient and effective.